COMPLEXITY OF THE TEXT: ABDULLA QODIRIY’S “O‘TGAN KUNLAR” (TRANSLATED INTO ENGLISH BY H. KAMILOV) - Xatamova Sojida Sobir qizi,; Jo‘rayev Muhammadrahimxon Murod o‘g‘li, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  the  study  of  text  complexity  has  gained  significant  attention  in modern  linguistics  and  discourse  analysis,  as  it  encompasses  the  interaction  of linguistic  structure,  meaning,  and  cognitive  comprehension.  Understanding  how sentence length, vocabulary, and semantic coherence affect readability is essential not only  for  education  but  also  for  literary  translation  and  comparative  stylistics.  This research aims to investigate the linguistic complexity of Abdulla Qodiriy’s “O‘tgan kunlar”  (translated  into  English  by  H.  Kamilov)  through  both  quantitative  and qualitative analysis. The Flesch–Kincaid readability formula is employed to calculate the difficulty level of the text, while theoretical perspectives by Walter Kintsch (1998) and Arthur C. Graesser (2011) are used to interpret how comprehension depends on linguistic and conceptual integration. The study seeks to demonstrate that classical Uzbek  prose,  despite  translation,  retains  its  semantic  richness  and  syntactic sophistication, reflecting the depth of cultural and emotional expression characteristic of Qodiriy’s literary art.